What is This Thing Called Adat Logic? - Qusthan A. H. Firdaus (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2022)
The notion of adat (or custom) law does not encourage people in philosophy to reveal its logic. This article aims to investigate the possibility of adat logic, its variety, and a possible common ground or thesis among its own kinds. In general, the adat logic means the true contradiction between the rigidity and the reflexibility of custom. In other words, it resembles the idea of dialetheia in modern logic, but it does not mean that the adat logic is a subdivision of the former. To seek a thesis of adat logic is to discuss the Javanese and Minangkabaunese adat logics, and I transform both logics into some notations for the sake of avoiding unnecessary linguistic challenges and hurdles. Thus, I insert each notation of a particular adat logic into the general notation of adat logic. By doing so, I wish to discover a common ground between some different adat logics.